2021
DOI: 10.1021/acsaem.1c03000
|View full text |Cite
|
Sign up to set email alerts
|

Boron in Ni-Rich NCM811 Cathode Material: Impact on Atomic and Microscale Properties

Abstract: Doping of Ni-rich cathode active materials with boron is a promising way to improve their cycling stability and mitigate their degradation, but it is still not understood how this effect is achieved and where the boron is located. To receive deeper insights into the impact of doping on atomic and microscale properties, B-doped Li[Ni 0. 8 Co 0.1 Mn 0 .1 ]O 2 (NCM811) cathode materials were synthesized by a hydroxide coprecipitation as a model compound to verify the presence and location of boron in B-doped, Ni-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 72 publications
(119 reference statements)
1
23
0
Order By: Relevance
“…Pristine and B-doped cathode active materials were synthesized by a hydroxide coprecipitation route reported before. 27 The whole synthesis was performed under a replenished argon atmosphere. Aqueous solutions of 2 M NaOH (Sigma-Aldrich, 98%) and 10 M NH 3 (aq) (Alfa Aesar, 28%) (solution 2) were prepared.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Pristine and B-doped cathode active materials were synthesized by a hydroxide coprecipitation route reported before. 27 The whole synthesis was performed under a replenished argon atmosphere. Aqueous solutions of 2 M NaOH (Sigma-Aldrich, 98%) and 10 M NH 3 (aq) (Alfa Aesar, 28%) (solution 2) were prepared.…”
Section: Methodsmentioning
confidence: 99%
“…Pristine and B-doped cathode active materials were synthesized by a hydroxide coprecipitation route reported before . The whole synthesis was performed under a replenished argon atmosphere.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The peak at 3.8/3.72 and 4.22/4.18 V corresponds to the Ni 2+ /Ni 4+ and Co 3+ /Co 4+ , respectively. 55 It is worth mentioning that the transition from H2 to H3, which takes place above the 4.2 V vs Li/Li + , results from the lattice shrinkage in the c direction, leading toward the structural degradation and performance fading. 56 Hence, an operating potential window of 3.0−4.2 V vs Li/ Li + was selected to perform the rest of the electrochemical experiments.…”
Section: Electrochemical Performancementioning
confidence: 99%
“…This not only improved rate performance and cyclability but also improved structural stability [88]. The mechanism behind the B-doping benefit is not fully understood, but one study suggested that B-doping affected crystal structure and cation disorder [89]. In NMC622, B-doping was found to change the microstructure of primary particles significantly and doping alone provided a marginal benefit to structural and electrochemical stability.…”
Section: Nmcmentioning
confidence: 99%